A synopsis of the genus Malesherbia (Passifloraceae) in Peru - Beltrán, Hamilton (2018)
We present 15 taxa of Malesherbia occurring in Peru, adding a new record, Malesherbia auristipulata. Updated data for departamental distribution, altitudinal range, and a species key are provided.